Exploring the validity of allostatic load in pregnant women. (March 2020) - Li, Yang; Dalton, Vanessa K.; Lee, Shawna J.; Rosemberg, Marie-Anne S.; Seng, Julia S.
Abstract: Background: The theory of allostatic load has gained momentum in perinatal research to understand the biological pathways of the impact of maternal chronic stress on adverse perinatal outcomes. However, due to physiological changes of pregnancy, including large variations across gestation, the extent to which allostatic load measured in pregnancy is valid has not been queried in depth. Objectives: This study aimed to assess the gestational patterns of selected individual allostatic load indicators and to explore whether a pregnancy allostatic load index score had face validity in relation to chronic sociodemographic stress. Design: This is a secondary analysis using data from the 1999–2006 National Health and Nutrition Examination Survey. Methods: A total of 1056 pregnant women were included for analyses. Using ten physiological indicators commonly included in an index of allostatic load, we described individual indicator and index score patterns across gestation and assessed differences in allostatic load index scores between women with and without sociodemographic stress. Findings: The average allostatic load index score at any gestational month was not statistically significantly different from the average allostatic load index score in the non-pregnant sample. We also found the allostatic load index score remained steady across gestational month, despite very different gestational patterns of individual allostatic load indicators, as long as gestation-specific risk quartiles were used to calculate the allostatic load index score. Face validity was affirmed via higher allostatic load index scores in women with sociodemographic stress compared to those without such stress. Conclusion: Our study suggests that measuring allostatic load in pregnancy is valid for reflecting women's true physiological functions and chronic stress, but gestational age should be considered when scoring the allostatic load index for women at different gestational age. Implications for practice: As a valid measure of chronic stress, a pregnancy allostatic load index may contribute to research on health inequities and perinatal outcomes.